The Usage of Extract of Purple Fleshed Sweet Potato (Ipomoea batatas L.) as Color of Lipstick - Rety Setyawaty; Desi Noviani; Dewanto Dewanto (Majalah Obat Tradisional, 2020)
Purple fleshed sweet potato (Ipomoea batatas L.) is one of the natural ingredients that contain natural colour pigments are anthocyanin. Anthocyanin is a water soluble pigments which is naturally found in various type of plants. This study aims to make lipstick preparations using the purple fleshed sweet potato extract (Ipomoea batatas L.) as a natural dye. The method is used to get anthocyanin as a color of lipstick by using maceration extraction method. The weight of sample is 250 grams of dried fleshed purple sweet potato. The liquid for maceration used of 95% ethanol. The condition of maceration is acid by using 2% of citric acid. The filtrate of maceration process must be thickened. The basis of lipstick components consisted of cera alba, lanolin, cetyl alcohol, paraffin solid, oleum ricini, propylene glycol, and nipasol. The concentration of fleshed purple sweet potato extract is 0%, 2.4%, 4.5% and 14.6%. The result of research is that the lipstick is easy to apply, unstable color, homogenous, melting point above 500C, pH of 6 and all lipstick have an breaking point when load at 330 grams. Extract of purple fleshed sweet potato can’t be used as a pigment color in the manufacture of lipstick but additional material is needed that can keep the lipstick color from being degraded by pH, storage temperature, light, enzymes, oxygenation, sugar, structural differences in anthocyanins and concentrations of anthocyanins.